The challenges of implementing carbon tax in Indonesia - Meilinda Stefani Harefa; Vebry M. Lumban Gaol; Halomoan Sihombing; Sri Ida Royani Simanjuntak; Prans Hotmaringan Hutabarat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Carbon taxes have proven to be an effective economic instrument in reducing carbon emissions in countries such as Finland, Sweden and Singapore. These countries have not only succeeded in significantly reducing greenhouse gas emissions but also utilised this policy to encourage the transition to clean energy while creating sustainable economic incentives. However, in Indonesia, the implementation of carbon tax has been delayed several times. This study aims to analyse the factors that cause delays in the implementation of carbon tax in Indonesia and expected to provide practical and applicable recommendations to ensure that the carbon tax can be effectively implemented by 2025. This research uses a qualitative approach. Thematic analysis is used to analyse data by reducing various qualitative data to find relevant and meaningful patterns in accordance with the research objectives. The factors that become obstacles in the implementation of carbon tax in Indonesia are unfinished regulations, readiness of digital infrastructure and technology, company dependence on fossil energy, and consideration of Indonesia's economic conditions. Specifically, the gap in digital monitoring technology still under development in terms of funding and human resources represents a significant barrier, causing Indonesia to lose momentum in integrating a low-carbon economy.